2017
DOI: 10.22158/rhs.v2n2p79
|View full text |Cite
|
Sign up to set email alerts
|

Data Envelopment Analysis for Relative Efficiency Measurement of Chinese Hospitals: A Systematic Review

Abstract: The purpose was to explore the gap between China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Therefore, it is necessary to investigate and select an appropriate index for using the DEA method. [ 37 ] Binder and Rudolph, in another study entitled “The systematic review of health care centers efficiency measurement” reviewed 21 studies and concluded that efficiency measurement of healthcare organizations has direct effect on their policy. They found that the difference in efficiency determined by DEA and SFA methods is due to various factors such as statistical errors, input and outputs definitions, and available data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to investigate and select an appropriate index for using the DEA method. [ 37 ] Binder and Rudolph, in another study entitled “The systematic review of health care centers efficiency measurement” reviewed 21 studies and concluded that efficiency measurement of healthcare organizations has direct effect on their policy. They found that the difference in efficiency determined by DEA and SFA methods is due to various factors such as statistical errors, input and outputs definitions, and available data.…”
Section: Discussionmentioning
confidence: 99%
“…DEA can be easily used for calculating efficiency scores based on the proper selection of input and output indicators. [ 37 ] The DEA method and different input and output variables have been used in most studies conducted in Iran, and SFA has been less considered. In the present study, the DEA method in governmental educational hospitals showed a higher efficiency than SFA method in the hospitals under study.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested in literature that in technical efficiency measurement, some monetary indicators such as total revenue, operational revenue, total expenditure, fixed assets, and so on should not be included so as to differentiate technical efficiency from allocative efficiency. [12][13][14] In this study, we only selected volume indicators as the input and output indicators. As CHSCs also provide public health services, some typical output indicators closely related to public health are also selected, such as number of physical examinations, number of discharged patients, number of health records, and so on.…”
Section: Selection Of Input and Output Indicatorsmentioning
confidence: 99%
“…[9][10][11] Moreover, it is suggested that the selection of input and output indicators among Chinese health care organizations needs to be standardized for more scientific estimation of efficiency scores. 12,13 The purpose of this study is to introduce Bootstrap-DEA method to estimate the technical efficiency of CHSCs in Wuhan city of China, to discuss possible policy implications for both Wuhan and other cities to further improve technical efficiency of CHSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Data Envelopment Analysis (DEA) has been widely applied to calculate the productivity and e ciency of healthcare institutions due to the characteristics of multiple inputs and multiple outputs (9). Furthermore, the Malmquist Productivity Index (MPI) model has been employed to indicate the dynamic productivity and e ciency changes of healthcare institutions or health systems (10,11).…”
Section: Introductionmentioning
confidence: 99%